Development Of Character-Based Learning Methods In Computer Aided Design (CAD) Courses - Ari Dwi Nur Indriawan Musyono; Murdani; Samsudi; M. Khumaedi; Sudiyono; Wahyudi; Sonika Maulana; Rizqi Fitri Naryanto (Jurnal Pendidikan Teknik Mesin, 2024)
Competence as a mastery possessed by a person needs to be improved with the right method. This study aims to develop a character-based learning method in the Computer Aided Design (CAD) course, improve learning outcomes and determine the increase in competence. The method used is an experiment, with a classroom action research approach. The learning process is managed with group management based on character suitability. The sample is students who take the CAD course. The results of the study showed that the character learning management model received very good criteria. This criterion is based on statements from students and lecturers. The results of the learning process can be concluded that learning grouping can be used to improve the competence of student learning outcomes in sketch material. This can be seen from the first reflection test of 40 students, 9 (22%) met the competency standard, reflection II 31 (78%) students met the standard and reflection III only 1 student did not meet it, in addition there was an increase in learning outcomes from a score of 66 to 80.